Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 1 - Section 1.6 - Transformations of Functions - Exercise Set - Page 245: 155



Work Step by Step

Step 1. Given $f(x)=x^2+3x+2$, we have $f(x+h)=(x+h)^2+3(x+h)+2=x^2+2xh+h^2+3x+3h+2$ Step 2. We have $f(x+h)-f(x)=2xh+h^2+3h$ Step 3. Thus $\frac{f(x+h)-f(x)}{h}=2x+h+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.